Everyday Earth and space science mysteries : stories for inquiry-based science teaching - Konicek-Moran, Richard (Arlington, VA : NSTA Press, National Science Teachers Association, 2013)
Presents everyday questions such as "Where to puddles go?" to motivate students to learn through hands-on science investigations.
Includes bibliographical references and index.
Professional
Professional.
Bureche Teacher Resource Library.
Keywords: Geology -- Study and teaching; Space sciences -- Study and teaching; Storytelling in education; Inquiry-based learning; Induction (Logic) in children; Geology -- Study and teaching; Space sciences -- Study and teaching; Storytelling; Learning and scholarship; Logic